INDIRECTNESS OF REQUESTING IN PASHTO LANGUAGE - Dr. Mian Shah Bacha, Dr. Tribhuwan Kumar, Bakht Sheema Bibi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research study aims at finding out the requesting pattern of indirectness in the Pashto language. The methodology for the study used was to gather the data by using the open role play situations adopted from Reiter`s (2000) Study and further more for data analysis, Cross Cultural Speech Act Realization Project (CCSAR) of Blum-Kulka, House and Kasper was applied to know the phenomenon of indirectness in the Pashto language. Moreover, the uses of conventional indirectness and non-conventional indirectness have also been noticed. The Pashto language respondents made a marked preference for conventional indirectness and their request forms were less tentative but they were cognizant of their relationship role to the addressors. It is further concluded that the Phenomenon of conventional indirectness was more frequent and thus, on the basis of the findings of the study, Pashto language should be considered a polite language.